A comparison of the role of dynorphin in the hippocampal mossy fiber pathway in guinea pig and rat - Salin, PA (J Neurosci, 1995)
Several behavioral studies in rat (Gallagher, 1988) have suggested that opioids in the hippocampus could play an important role in learning and memory. However, in this species, very few reports specifically address the issue of physiological actions of opioids released by the mossy fibers which constitute the principal source of dynorphin and enkephalin in the hippocampus. In the guinea pig high frequency stimulation of mossy fibers causes a transient heterosynaptic inhibition of neighboring mossy fibers (Weisskopf et al., 1993) or perforant path synapses in the dentate (Wagner et al., 1993), which is mediated by the synaptic release of dynorphin that activates presynaptic kappa receptors. We show here that neither exogenous nor endogenous dynorphin affect mossy fiber excitatory postsynaptic potentials in the Sprague-Dawley rat, which is consistent with the finding that kappa receptor binding in the mossy fiber termination zone is dense in the guinea pig and sparse in this rat. More surprisingly, although kappa receptor binding is found in the rat dentate gyrus molecular layer and in the CA3 pyramidal cell layer, dynorphin had no action on perforant path field responses, somatic potassium currents or evoked monosynaptic inhibitory postsynaptic currents in CA3 cells. This lack of action appears to be an exception among rodents as dynorphin significantly inhibited mossy fiber responses in the hamster, mouse, and even another strain of rat, Long-Evans. Unlike the kappa mediated actions, the mu opioid receptor agonist DAMGO inhibited Sprague-Dawley mossy fiber responses, as it does in guinea pig. In contrast to other investigators, however, we found that the opioid receptor antagonist naloxone had no effect on Sprague-Dawley mossy fiber LTP.